Probabilities, delays and social distances: decision-making in different domains - Castillo, Geoffrey (2017)
I start the thesis with a focusing model in which increasing the range of values of an attribute makes the decision-maker place more weight on this attribute. This model explains the documented communality between risky choice and intertemporal choice, and provides a unique explanation to the common ratio, common delay, and magnitude effects. It also captures preference reversals between choice and valuation, and different forms of context dependence such as the asymmetric dominance effect. Since the model is not restricted to probabilities and temporal delays, I also apply it to allocations characterised by an amount of money and a social distance. It predicts ‘common social distance’ effects, magnitude effects in the social domain, and preference reversals between choice and valuation of allocations.